SLEEP TIME MANAGEMENT OF STUDENTS (CASE STUDY AT PPMI ASSALAAM) - asyhuri, asyhuri (Jurnal Ilmiah Pesantren, 2023)
This study aims to examine the sleep time management of students at PPMI Assalaam and its impact. The method used in this research is qualitative. Data acquisition is based on findings in the field and with a literature approach. The research was conducted in December 2021. The data analysis technique used in this research is descriptive qualitative and interpretive, namely describing and giving meaning to the analyzed data to find relationships between various concepts. In this study, it was found that the rules for sleeping time for students at PPMI Assalaam were in the Tibsar (Santri Basic Order). Eighty percent of santri are obedient (sleeping according to the rules in tibsar) while fifteen to twenty percent of santri are disobedient. From the results of the study, it is recommended: (1) Tibsar published in 2019 article 29 regarding sleep there is no rule for napping for students so it needs to be rearranged. (2) There is a need for enlightenment of insight about sleep time management among students. (3) It needs to be clarified in chapter X Dormitory, article 28 number 6, regarding students not being allowed to turn off the bedtime light at bedtime. (4) To meet the sleeping hours of students (medical standards) it is necessary to have a new policy that supports sleep time management according to the sunnah of the apostle and medical. (5) In Tibsar, it is necessary to add a balanced reward and punishment.